(4x-2)/9=-9

Simple and best practice solution for (4x-2)/9=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-2)/9=-9 equation:



(4x-2)/9=-9
We move all terms to the left:
(4x-2)/9-(-9)=0
We add all the numbers together, and all the variables
(4x-2)/9+9=0
We multiply all the terms by the denominator
(4x-2)+9*9=0
We add all the numbers together, and all the variables
(4x-2)+81=0
We get rid of parentheses
4x-2+81=0
We add all the numbers together, and all the variables
4x+79=0
We move all terms containing x to the left, all other terms to the right
4x=-79
x=-79/4
x=-19+3/4

See similar equations:

| (29-7y)+7y=29 | | 8=15+w/4 | | 152=x+164 | | (5x+4)-(2x+5)=24 | | y/2-16=13 | | 4x^2+2=-7x-3 | | 3x-5=5×-13= | | 4x-11x=0 | | 3(5+a)=21-5a | | 176x-1=41 | | 64x²-9=0 | | |4x-7|=21 | | c/2+2=5 | | 118=x+164 | | |-3z+5|=|-7z+10| | | X/4x=25 | | (x+10)=55° | | 31=x+164 | | r+–76=–37 | | 2x5+x+35=45 | | 3−29b=13b−73−29b=13b−7 | | 9p−10=24+p | | -3(2y+3)=-10(y+3) | | x²-4x-88=0 | | -(x+2)=4(x+1) | | 9/p-10=2/4+p | | 28=x+164 | | -6(1+v)=2(1+-3v)+-8 | | G(0)=x*2+3 | | 3n+20=4n-7 | | b-6/3=1 | | 6=-5(c+4)=10 |

Equations solver categories